Echocardiographic Profile of Patients in Dhulikhel Hospital, A Medical College Hospital in Nepal - Humagain, Sanjaya; Twayana, Ramsundar; Koju, Rajendra (Nepalese Heart Journal, 2014)
Background and Aim : Echocardiograph is an important diagnostic tool to evaluate cardiac disease and is indispensible for management. So it is important to know the spectrum of cardiac abnormalities that can be detected by echocardiograph and the frequency of these findings may vary depending on where the echocardiogram is performed. Aim of this study was to find out the spectrum of echocardiographic finding in different age group in a medical college hospital. Methods and materials : A retrospective observational study was done to at Dhulikhel Hospital to review Echocardiographic profile of 3310 patients who were indicated for echocardiogram over a period of 3 years. Data collected from echocardiograph report registry. Data analysis was done using SPSS 17. Result : Congenital Heart Disease(CHD) (37.74%),Normal finding( 21.19%), Pericardial Heart Disease(19.21%) and Rheumatic Heart Disease(RHD)(17.88%) were the echocardiographic finding in children. In adolescents and young adults Rheumatic Heart Disease (49.90%), Hypertensive Heart Disease (13.34%), Congenital Heart Disease (6.58%), and Pericardial Disease (4.38%) were found. Most common finding in middle age was cor-pulmonale (34.76%) followed by Diastolic Dysfunction (20.60%), Hypertensive Heart Disease(17.06%),Ischemic Heart Disease(IHD) (12.80%). In elderly age most common finding was Diastolic Dysfunction (57.14%). Conclusion : The spectrum of echocardiograph finding in a medical college hospital ranges from Congenital Heart Disease, Rheumatic Heart Disease, Ischemic Heart Disease ,Pericardial disease, Corpulmonale, Diastolic Dysfunction, systolic dysfunction and degenerative valve disease. Streptococcal sore throat leading to Rheumatic Heart Disease and complication of tuberculosis and parasitic infestation leading to pericardial diseases, as well as Hypertensive Heart Disease, and Ischemic Heart Disease constitutes burden in Nepal. Cor-pulmonale and ) Sanjaya Humagain, Ramsundar Twayana, Rajendra Koju. DOI: http://dx.doi.org/10.3126/njh.v11i1.10976 Nepalese Heart Journal 2014;11(1): 13-17